Chapter IV: Rates and Derivatives (Quarterly Journal of Economics, 1938)
Journal Article Chapter IV: Rates and Derivatives Get access The Quarterly Journal of Economics, Volume 52, Issue Supplement, May 1938, Pages 93–116, https://doi.org/10.1093/qje/52.Supplement.93 Published: 01 May 1938